2017
DOI: 10.3390/ijerph14111356
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sports Participation across Transition to Retirement: Modification by Migration Background and Acculturation Status

Abstract: While total physical activity decreases over the life course, sports and leisure-time physical activity (LTPA) have shown to increase after transition to retirement. This paper aimed to investigate whether this change in sports participation differs (1) between non-migrant persons (NMP) versus persons with a migrant background (PMB), and (2) by acculturation status. Data was drawn from 16 waves of the German Socio-Economic Panel Study (SOEP) including 2664 NMP and 569 PMB. PMB were grouped according to accultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Even so, also in the men’s shot put and discus throw there was an accelerated decline in performance after the age of 70, despite the decrease in the mass of the discus and put thrown. While the increase in numbers of athletes in these disciplines after retirement ( Engberg et al, 2012 ; Schönbach et al, 2017 ) will result in an increased proportion of less-performing athletes that undoubtedly accentuate the population-based accelerated decline in performance after the age of 70, in the running disciplines participation numbers are not showing a large increase after the age of 70 ( Figures 1 , 2 ). Thus, overall there appears to be an accelerated decline in performance after the age of 70 years.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, also in the men’s shot put and discus throw there was an accelerated decline in performance after the age of 70, despite the decrease in the mass of the discus and put thrown. While the increase in numbers of athletes in these disciplines after retirement ( Engberg et al, 2012 ; Schönbach et al, 2017 ) will result in an increased proportion of less-performing athletes that undoubtedly accentuate the population-based accelerated decline in performance after the age of 70, in the running disciplines participation numbers are not showing a large increase after the age of 70 ( Figures 1 , 2 ). Thus, overall there appears to be an accelerated decline in performance after the age of 70 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported on the long-term trajectories of PA patterns across the retirement transition indicating that PA tends to increase right after retirement but declines later on [91,99,102,104,105]. In contrast, two studies found evidence that PA levels remained stable after an initial increase [101,108]. Findings for the pre-retirement period were ambiguous with reported increases and decreases in PA [102,105] depending on domain and gender.…”
Section: Employment-related Events and Transitionsmentioning
confidence: 99%
“…The papers of Nazroo [ 6 ], Hoebel et al [ 7 ], Schönbach et al [ 8 ], and Schoenmakers et al [ 9 ] focus on social inequality and health among the elderly, alternatively investigated under a class or ethnicity-cultural lens.…”
Section: Social Inequality and Health Among The Elderly And Inequamentioning
confidence: 99%
“…Schönbach et al [ 8 ] provide deeper insight into an example of health-related behavior and show that physical activity as a key factor of healthy aging, measured as sports participation, takes a positive leap at entry to retirement, but social differentials remain. A migrant background as well as the level of acculturation only had minor effects on the enhanced post-retirement physical activity levels in this analysis of German Socio-Economic Panel data.…”
Section: Social Inequality and Health Among The Elderly And Inequamentioning
confidence: 99%
See 1 more Smart Citation